2001
DOI: 10.1139/f01-167
|View full text |Cite
|
Sign up to set email alerts
|

How robust are Bayesian posterior inferences based on a Ricker model with regards to measurement errors and prior assumptions about parameters?

Abstract: We present a Bayesian approach of a Ricker stock-recruitment (S/R) analysis accounting for measurement errors on S/R data. We assess the sensitivity of posterior inferences to (i) the choice of Ricker model parameterizations, with special regards to management-related ones, and (ii) prior parameter distributions. Closed forms for Ricker parameter posterior distributions exist given S/R data known without error. We use this property to develop a procedure based on the Rao-Blackwell formula. This procedure achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…A long series of data (20 years) has been collected on ecological characteristics, as well as on the distribution and abundance of salmon within the river. Previous papers utilizing these data focused on analysing the stock-recruitment relationship, and showed that average recruitment and smolt production in the River Oir was relatively low compared with northern European and Canadian rivers Rivot et al, 2001Rivot et al, , 2004. Moreover, the research facilitated the development of tools for decision analysis related to the sustainable management of salmon fisheries at a regional level (Prévost and Porcher, 1996;Rivot et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A long series of data (20 years) has been collected on ecological characteristics, as well as on the distribution and abundance of salmon within the river. Previous papers utilizing these data focused on analysing the stock-recruitment relationship, and showed that average recruitment and smolt production in the River Oir was relatively low compared with northern European and Canadian rivers Rivot et al, 2001Rivot et al, , 2004. Moreover, the research facilitated the development of tools for decision analysis related to the sustainable management of salmon fisheries at a regional level (Prévost and Porcher, 1996;Rivot et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous papers utilizing these data focused on analysing the stock-recruitment relationship, and showed that average recruitment and smolt production in the River Oir was relatively low compared with northern European and Canadian rivers Rivot et al, 2001Rivot et al, , 2004. Moreover, the research facilitated the development of tools for decision analysis related to the sustainable management of salmon fisheries at a regional level (Prévost and Porcher, 1996;Rivot et al, 2001). Here, we analyse the data series with two main objectives: (i) to evaluate the river's salmon production and the status of the population; (ii) to analyse the evolution of the parameters of Atlantic salmon population dynamics in a stream in relation to variance in the environment, including especially the impact of anthropogenic activities in the drainage basin.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study we only consider the simplest case, in which perturbation is a random positive constant. Although such type of perturbation exists in real world [33,34] , there are many different types of perturbations which could exist, such as the density dependent [35,36] and independent normal distributions [37][38][39] . Moreover, different types of perturbations could have different biological meanings and also may result in different dynamic behavior for population models.…”
Section: Biological Conclusion and Discussionmentioning
confidence: 99%
“…And certainly it is the case that the spectrum of dynamical behaviours emanating from this model can be found in nature (Turchin and Taylor, 1992;Dennis and Taper, 1994;Cushing et al, 1996;Cushing et al, 2003). There are abundant applications of this model in fisheries and wildlife (Paulik and Bayliff, 1967;McCarthy, 1996;Elliott et al, 1997;Saitoh et al, 1997;Myers and Mertz, 1998;Halls et al, 2000;Chen and Irvine, 2001;Rivot et al, 2001;Taper and Gogan, 2002;McCarthy et al, 2003;Travis, 2003;Zheng and Kruse, 2003).…”
Section: Models and Methodsmentioning
confidence: 99%